Handbook of food and bioprocess modeling techniques - Sablani, Shyam S. (Shyam Swaroop), 1964- (Food science and technology (Taylor & Francis), 2007)
The publication of the Handbook of Food and Bioprocess Modeling Techniques brings together for the first time in one volume all the conventional and emerging modeling techniques currently available. Calling on the most recognized specialists in the industry, the editors have succeeded in creating an indispensable reference. Rather than promote one modeling system, this volume looks at the pros, cons, and proper applications of every significant, contemporary modeling system. With numerous examples in food industry applications, this volume is a valuable resource for professionals and students.